Electromagnetic fields near a concave perfectly conducting cylindrical surface - Ercan, Topuz; Edip, Niver; Leopold B., Felsen (Institute of Electrical and Electronics Engineers (IEEE), 1982)
Summary: From the summary: ''As the source and/or observation points move off a boundary, the number of relevant multiply reflected rays decreases, and the caustics eventually become separated sufficiently to be treated as isolated. Ray optics is then expected to apply provided that uniform corrections near caustics and their endpoints are included. This conjecture is confirmed in the present investigation, which tracks the field continuously from the `boundary layer' near a concave surface, where ray optics is invalid, to off-surface points where it applies.''.
Keywords: Waves and radiation in optics and electromagnetic theory; Geometric optics